METODE PEMETAAN POLITIK UNTUK PEMILIHAN UMUM KEPALA DAERAH PILKADA KOTA SALATIGA 2017 - Suwardi, - (Transformasi, 2016)
Political mapping survey method for local election of Salatiga Town’s Major must concernabout time range until the election day (D). The survey that done in a year before the electionday is different in some component: (1) survey location spot; (2) object data; (3) instrumentdata; (4) operation field research control; (5) analytical technic.Key word: local election, method, research, frame work